Analgesic and antipyretic activity of Tri-Sa-Maw recipe - Urarat Nanna (2018)
© 2015, Medical Association of Thailand. All rights reserved. Background: Tri-sa-maw recipe is composed of equal proportions of the three fruits including Terminalia chebula Retz., Terminalia sp. and Terminalia bellirica Roxb. In Southeast Asia, these fruits are used as both food and medicine. In Thai traditional medicine, Tri-sa-maw recipe is well known for treating fever, expectorant, periodic maintenance, and tight stomach relief. Objective: To study anti-inflammatory, analgesic and antipyretic activities of Tri-sa-maw recipe in experimental animals. Material and Method: The anti-inflammatory study was conducted by two experimental models; ethyl phenylpropiolateinduced ear edema and carrageenin-induced paw edema. For analgesic activity, the pain was induced by acetic acid or heat. In addition, yeast-induced hyperthermia was performed for the study of antipyretic activity. Results: The results showed that Tri-sa-maw recipe extract reduced ear edema of rat induced by EPP but did not inhibit acute inflammation in the carrageenin-induced paw edema. However, the extract at the doses of 300-1,200 mg/kg was able to inhibit the acetic acid-induced writhing response, but not the heat-induced pain. This result suggests the peripheral effect of its analgesic activity, which inhibits the biosynthesis, and/or release of some pain mediators. Finally, oral administration of the extract at the dose of 1,200 mg/kg body weight effectively reduced the hyperthermia, which possibly is due to the inhibition of prostaglandins. Conclusion: The present study has clearly demonstrated both analgesic and antipyretic activities of Tri-sa-maw recipe.